Regeneration characteristics of selection felled forest gaps of different ages in the evergreen forests of Sholayar, Kerala, India - Rajesh, N. (2018)
A field study was conducted in the wet evergreen forests of Sholayar in the Western Ghats to characterise vegetation development as a function of time after selection felling. Four quadrats (40 x 40 m) were established in selected patches of forests selection felled 7,16, 21 and 28 years before 1992. All trees and shrubs (> 10 cm girth at breast height) were enumerated. Species-wise counts of seedlings (<10 cm GBH) were also made in four 5 x 5 m quadrats within each of the main quadrats. In addition, soil physico-chemical properties (top 15 cm layer) such as moisture content, pH, organic C, total N, available P and K were evaluated. The current suite of species in the selection felled forest gaps exhibited both early and late serai characteristics. About 62 to 83% of the tree species encountered at these sites (logging coupes) were, however, common. Further, the relative proportion of early and late successional species was dependent on gap age. As the gap age increased, abundance of late successional species such as Palaquium ellipticum, Mesua nagassarium and Vateria indica increased. Floristic diversity declined as time after gap formation increased. Moreover, floristic diversity indexes were generally lower than many other formations in the Western Ghats. Soil moisture content, organic C, N and K levels were high at the 7- and 16- year-old sites compared to the 21- and 28- year-old sites.